2021
DOI: 10.1038/s41550-021-01445-6
|View full text |Cite
|
Sign up to set email alerts
|

Slowly cooling white dwarfs in M13 from stable hydrogen burning

Abstract: White Dwarfs (WDs) are the final evolutionary product of the vast majority of stars in the Universe. They are electron-degenerate structures characterized by no stable thermonuclear activity, and their evolution is generally described as a pure cooling process. Their cooling rate is adopted as cosmic chronometer to constrain the age of several Galactic populations, including the disk, globular and open clusters. By analysing high-resolution photometric data of two twin Galactic globular clusters (M3 and M13), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…Also, residual nuclear burning down to advanced evolutionary stages of WD evolution is allowed. The role played by residual H burning is not negligible (see Chen et al 2021, for recent observational evidence of quiescent thermonuclear activity occurring in cooling WDs) and by the time evolution reaches the ZZ Ceti domain, it has yielded a substantial reduction of the H content with which the WD enters its cooling branch.…”
Section: New Wd Evolutionary Modelsmentioning
confidence: 99%
“…Also, residual nuclear burning down to advanced evolutionary stages of WD evolution is allowed. The role played by residual H burning is not negligible (see Chen et al 2021, for recent observational evidence of quiescent thermonuclear activity occurring in cooling WDs) and by the time evolution reaches the ZZ Ceti domain, it has yielded a substantial reduction of the H content with which the WD enters its cooling branch.…”
Section: New Wd Evolutionary Modelsmentioning
confidence: 99%
“…However, unlike ω Cen, M13 is not known to host extreme He-rich stars that can form He-core WDs from single stellar evolution. Chen et al (2021) suggested that the bright WDs in M13 are the result of slow cooling due to the residual hydrogen burning on the C/O WD surface. Hence, it is possible that some of the FUV-detected WDs in ω Cen are such slowly cooling C/O WDs.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…In searching for the optical companion to PSR J1835 −3259A and PSR J1835−3259B, we adopted the so-called "UV-route," a photometric procedure specifically optimized for the identification of blue and hot objects in crowded fields such as hot horizontal branch stars, blue straggler stars, and WDs and widely used by our group in previous papers (see Ferraro & Paresce 1993;Ferraro et al 1997aFerraro et al , 1997bFerraro et al , 2001aFerraro et al , 2003bDalessandro et al 2013b). Specifically, in this paper we followed the approach described in Cadelano et al (2019Cadelano et al ( , 2020; see also Raso et al 2017Raso et al , 2020Chen et al 2021Chen et al , 2022.…”
Section: Data Reductionmentioning
confidence: 99%